Externally assessed psychosocial work characteristics and diagnoses of anxiety and depression. Issue 2 (23rd January 2008) - Waldenström, K; Ahlberg, G; Bergman, P; Forsell, Y; Stoetzer, U; Waldenström, M; Lundberg, I
Abstract : Background: Interpretations of relationships between work characteristics and psychiatric disorders may be biased by over-reporting of unfavourable work characteristics among those with psychiatric disorders. This study attempts to account for this bias by using external assessments of work characteristics. Methods: Psychiatric symptoms were assessed in an interview and psychiatric diagnoses were established according to DSM-IV. Current work characteristics and work characteristics three years ago were assessed in an interview with predetermined criteria and included cognitive requirements, possibility of influence, and required conformance to schedule, time pressure, and hindrances concerning goals, resources and instrumental support. Deterioration in work characteristics during the study period was also assessed. The sample consisted of 672 employed men and women in different occupations. Results: Lack of instrumental support from colleagues and supervisors (OR 6.4, 95% CI 2.6 to 15.8) assessed as a hindrance to work performance, and deterioration in work characteristics during the study period (OR 2.8, 95% CI 1.3 to 6.1) were associated with increased odds ratios for depression after adjustment for confounding factors, including symptoms of mental illness at baseline. Findings for anxiety were similar but not statistically significant. Conclusion: Externally assessed lack of instrumental social support at work and deteriorating work characteristics were associated with an increased risk for depression.